City logistics – how to create an OD matrix for goods transports within the city of Oslo? - Jean-Hansen, Viggo; Andersen, Jadar (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
In this paper we will examine the advantages of using existing trade statistics to construct an OD matrix for freight transport for a city area. The OD matrix is constructed by examining how a wholesaler relate to the retailer industries. If this work is successful it will improve the quality of data quite substantially for city models. The result from use of such information may give more accurate results and have the potential for improving the planning of a city area. The outline of this paper will first be a stepwise recipe for constructing the OD –matrix and finally discuss some of the assumptions we have done in order to arrive to the result of construction of a matrix. We will finally discuss how robust is this method compared to survey data.